A Thirty-Year Experience With Head and Neck Flap Reconstruction. Issue 5 (July 2017) - Sun, Alexander Haosi; Xu, Xiaolu; Sasaki, Clarence Takashi; Ariyan, Stephan; Steinbacher, Derek Matthew
Abstract : Background: Head and neck (HN) defects after tumor extirpation can be challenging to repair. Historically, pedicled flaps were the mainstay for reconstruction, but recently, free tissue transfer has been preferred. This study compares patient characteristics and flap outcomes for HN defects over a 30-year period at the authors' institution. Methods: Head and neck cancer patients receiving flap reconstruction from 1983 to 2013 were included. Records were reviewed for demographic and perioperative data. Flap complications were compared and statistical tests were 2-tailed with a significance level of 0.05. Results: Eight hundred sixty-one patients fulfilled inclusion and exclusion criteria. Pedicled reconstruction predominated during early time-points (96.3% pedicled), compared with later years (69.5% free-tissue). Free flaps were associated with significantly longer operative times (643.5 versus 429.7 minutes, P <0.0001) and postoperative stays (16.89 versus 14.01 nights, P = 0.0005) and had higher rates of emergent reoperation, total flap loss, hematoma, and donor site morbidity. Previous irradiation did not affect major complication rate for either flap type. Conclusions: A shift from pedicled to free flaps for HN reconstruction occurred over the last 30 years. Free flaps had a higher complication profile in this cohort, which was largely accounted for by a higher return rate to the operating room compared with pedicled flaps (17.31% versus 5.46%, P <0.0001). Additionally, this complication profile may reflect the increasingly common use of free tissue flaps for more complex reconstructions. Several of these differences in complication rates between flap types were no longer significant in the last 5 years of this study.